ANALYSIS OF AFFECTING FACTORS SELF MONITORING OF BLOOD GLUCOSE IN TYPE 2 DIABETES MELLITUS PATIENTS - Ahmad J; Yulia; Muhammad Adam (Jurnal Kesehatan, 2022)
Self Monitoring Blood Glucose (SMBG) has been accepted as an important part of diabetes mellitus management. The purpose of this study was to identify factors that affect type 2 diabetes mellitus patients to perform SMBG. This is a cross sectional study, with 80 respondents. Statistical analysis was using a chi square correlation test and a multiple logistic regression. The result shows that there a significant correlation between belief on diabetes mellitus management and SMBG (p = 0,000). The most influential factor on SMBG is the belief variable on diabetes mellitus management with OR = 14,069 after controlled with the knowledge variable (95% CI OR 0,100 - 1983, 518). It is needed to improve the belief on diabetes mellitus managements especially in type 2 diabetes mellitus patient